Implicit Differentiation

Functions are described explicitly when one variable can be written in terms of another variable. For example y = 2x3 - 5 describes the variable y in terms of the variable x and thus is described explicitly.

EXPLICIT: one variable is described in terms of one other variable.


y = 2x3 - 5



In other situations functions are described implicitly using the relationship between the two variables such as, x4 + y2 = 1 - 5xy.

IMPLICIT: variables are NOT is described in terms of one other variable.


x4 + y2 = 1 - 5xy



Functions described implicitly can be differentiated without being written explicitly. This type of differentiation is called Implicit Differentiation.

To differentiate implicitly both sides of the equation are differentiated with respect to x and the resulting equation solved for y x .

Let's look at some examples:

To work these examples requires the use of various differentiation rules. If you are not familiar with a rule go to the associated topic for a review.


x2 + y2 = 36

Step 1: Differentiate the x-terms on both side of the equation with respect to x.

x ( x 2 + y 2 )= x 36


Apply Sum Rule.


x x 2 + x y 2 = x 36


Apply Power and Constant Rule.


2x+ x y 2 =0

Step 2: Differentiate the y-terms.


Factor x into y y x and take the derivative of y y 2 normally resulting in the derivative times y x .

2x+ x y 2 =0 Original


x y 2 = y y 2 y x =2y y x Implicit Diff.


2x+2y y x =0 Substitute

Step 3: Solve for y x and simplify.

Original


2x+2y y x =0


Subtract 2x to both sides:


2y y x =2x


Divide both sides by 2y.


y x = 2x 2y


Simplify


x y

Example 1:      3y3 - x3 = 5xy

Step 1: Differentiate the x-terms on both side of the equation with respect to x.

x (3 y 3 x 3 )= x 5xy


Apply Difference Rule.


x 3 y 3 x x 3 = x 5xy


Apply Constant Multiple Rule.


3 x y 3 x x 3 =5 x xy


Apply Power Rule.


3 x y 3 3 x 2 =5 x xy

Step 2: Differentiate the y-terms.


Factor x into y y x and take the derivative of y normally resulting in the derivative times y x .

Original


3 x y 3 3 x 2 =5 x xy


Implicitly differentiate 3 x y 3 using the power rule.


3 x y 3 =3 y y 3 y x =9 y 2 y x


Implicitly differentiate 5 x xy using the product rule.


5 x xy=5[ ( x ·1 ) y x +( y ·1 ) ]


5x y x +5y


Substitute into the original equation:


9 y 2 y x 3 x 2 =5x y x +5y

Step 3: Solve for y x and simplify.

Original


9 y 2 y x 3 x 2 =5x y x +5y


Add 3x2 to both sides:


9 y 2 y x =5x y x +5y+3 x 2


Subtract 5x y x from both sides.


9 y 2 y x 5x y x =5y+3 x 2


Factor out y x from the left-hand side:


y x ( 9 y 2 5x )=5y+3 x 2


Divide both sides by 9y2 - 5x.


y x = 5y+3 x 2 9 y 2 5x

Example 2:      ey = 2x - y

Step 1: Differentiate the x-terms on both side of the equation with respect to x.

x ( e y )= x ( 2xy )


Apply Difference Rule.


x e y = x 2x x y


Apply Constant Multiple Rule.


x e y =2 x x x y


Apply Power Rule.


x e y =2 x y

Step 2: Differentiate the y-terms.


Factor x into y y x and take the derivative of y normally resulting in the derivative times y x .

Original


x e y =2 x y


Implicitly differentiate ey using the natural exponent rule.


x e y = y e y y x = e y y x


Implicitly differentiate x y using the power rule.


x y= y y y x =1 y x


1 y x


Substitute into the original equation:


e y y x =21 y x

Step 3: Solve for y x and simplify.

Original


e y y x =21 y x


Add 1 y x to both sides:


e y y x +1 y x =2


Factor out y x from the left-hand side:


y x ( e y +1 )=2


Divide both sides by ey + 1.


y x = 2 e y +1





Related Links:
Math
algebra
Combination of Functions
Composition of Functions
Calculus Topics


To link to this Implicit Differentiation page, copy the following code to your site:


Educational Videos